Crystal Exergy Value (Wax) Crude Palm Oil (CPO) Influence Based On The Mixed Type - Istianto Budhi Rahardja; Rulan Dinary; Anwar Ilmar Ramadhan (Journal of Applied Sciences and Advanced Technology, 2019)
Liquid wax (wet wax) is a source of heat energy and lighting produced from palm oil to provide illumination where needed. The need for candles is used for lighting the environment, the place, and the heating of the objects for need. The manufacture of liquid candles is to provide the base oil of crude palm oil mixed evenly in the melting point of solid paraffin. Paraffin and CPO are melted together and placed, then cooled. The wax ignition process produces heat and light. Results that can be shown with a comparison between palm oil and solid paraffin will produce hardness, texture, and flame ignition. With 50 grams of paraffin, 50 gr CPO and 1 kg of oxygen (1: 5) of the fuel of 250 gr O2, will produce 1300 gr CO2, 1175gr H2O, -1487,5 gr O2 and 940 gr N2. Different paraffin granules, will produce the same product in energy balance, while the value of N2 remains. Experimental value from mixing CPO and paraffin by 50 gr: 50 gr yielding entropy generation (S gen) and CPO wax exudo of 257.16 kJ / kmol.K and 77,918.67 kJ/kmol and its value decreases based on paraffin administration